Does the Spirit Have a Story?: A Narrative Theology of the Holy Spirit - Thornhill, A. Chadwick (Journal of theological interpretation, 2020)
Narrative theology has brought a renewed focus to the nature of the Christian faith as a storied one. A helpful way to understand the unity of the biblical texts is through seeing an overarching metanarrative to the Bible. While this has been applied to various dimensions of Christian theology, it seems little narrative attention yet has been given to the Holy Spirit. This article will offer an initial construction of a narrative pneumatology through the application of narrative theology. The essay will examine the major movements of the Spirit of God through the Christian Scriptures to construct a narrative of the Spirit that can aid in understanding both the doctrine of pneumatology as well as the biblical story as a whole. After a discussion of narrative theology and other interpretive and methodological considerations, the article will offer the following narrative framework: (1) Spirit Vivifies Creation, (2) Spirit Departs Humanity, (3) Spirit Empowers Israel, (4) Spirit Departs Israel, (5) Spirit Returns through Messiah, (6) Spirit Revivifies Creation. The contribution will conclude with possible implications of such an approach for pneumatology as well as other avenues needing further research.